ÖPNV: Integrierte Managementsysteme. - Fritz, Holger; Lange, Jan; Schneider, Christian (Deutscher Verkehrs-Verl., 2009)
Die Regionalbus Braunschweig GmbH (RBB) - eine Busgesellschaft der DB Stadtverkehr GmbH, Region Nord - wurde Ende des Jahres 2008 erfolgreich nach ISO 9001 (Qualitätsmanagement), ISO 14001 (Umweltschutzmanagement) und OHSAS 18001 (Arbeitsschutzmanagement) zertifiziert. Neben den Grundlagen eines iMS wird in dem Artikel der Prozess der Implementierung dargestellt. Besonderes Augenmerk wird dabei dem Aufwand und Nutzen gewidmet, den ein entsprechendes Managementsystems mit sich bringt.

In order for companies engaged in public local transport (ÖPNV) to maintain their competitive strength, the essential prerequisites are to offer quality of service to customers and, on an internal basis, to ensure cost leadership as well as awareness of social responsibilities in relation to environmental protection, while also safeguarding industrial health and safety standards at workplaces. The successful implementation of an integrated management system helps to create the framework that covers quality of service (ISO 9001), environmental protection (ISO 14001), and security at the workplace (OHSAS 18001). Furthermore, management systems are ideally suited to help cope with the bewildering array of judicial demands, paragraphs and laws. They foster legal certainty and provide an impetus for the ongoing process of improvements.
The formation of integrated management systems and their introduction to public local transport (ÖPNV).
Keywords: Öffentlicher Verkehr; Bus; Regionalverkehr; Verkehrsunternehmen; Management; Prozesssteuerung; Nutzwertanalyse; Arbeitsschutz; Regionalbus; Qualitätsmanagement; Zertifizierung; Controlling